Islamic Education Personnel Management in the Digital Era - Hermawansyah Hermawansyah (Prodi PAI STIT Sunan Giri Bima, 2025)
The development of digital technology has significantly transformed the educational landscape, including human resource management in Islamic educational institutions. Personnel management has become a strategic aspect because it is directly related to the quality of teaching and non-teaching staff, who play a key role in the success of learning and the formation of student character. The digital era demands that Islamic educational institutions transform their personnel management, from strengthening digital competencies and adjusting leadership roles to changing organizational culture to be more adaptive and innovative. A literature review indicates a paradigm shift from traditional administrative practices to a more technology-based personnel management approach, adaptive competencies, and professional ethics. However, this transformation also faces challenges such as a digital skills gap, limited infrastructure, and resistance to change. Therefore, an effective personnel management strategy must integrate technology with Islamic values and encourage increased professionalism through responsive policies, effective organizational communication, and a work culture that supports innovation. This research is expected to provide an overview of the direction of personnel management in Islamic education that is relevant to digital developments and the needs of the times.